2003
DOI: 10.1046/j.1365-8711.2003.06163.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron abundances and heating of the intracluster medium in hydrodynamical simulations of galaxy clusters

Abstract: Results from a large set of hydrodynamical smoothed particle hydrodynamics (SPH) simulations of galaxy clusters in a flat ΛCDM cosmology are used to investigate the metal enrichment and heating of the intracluster medium (ICM). The physical modelling of the gas includes radiative cooling, star formation, energy feedback and metal enrichment which follow from the explosions of supernovae of type II and Ia. The metallicity dependence of the cooling function is also taken into account. The gas is metal‐enriched f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 87 publications
(207 reference statements)
7
83
0
Order By: Relevance
“…Mechanisms such as ram pressure (Domainko et al 2004;Cora 2006) or tidal stripping (e.g. Murante et al 2004) are currently being investigated with numerical simulations (see also Valdarnini 2003;Tornatore et al 2004). The same mechanisms are often invoked to explain the morphological evolution of the cluster galaxies' population.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms such as ram pressure (Domainko et al 2004;Cora 2006) or tidal stripping (e.g. Murante et al 2004) are currently being investigated with numerical simulations (see also Valdarnini 2003;Tornatore et al 2004). The same mechanisms are often invoked to explain the morphological evolution of the cluster galaxies' population.…”
Section: Discussionmentioning
confidence: 99%
“…Cosmological hydrodynamical simulations have been used with similar goals (Valdarnini 2003;Romeo et al 2006;Tornatore et al 2007;Davé et al 2008;Wiersma et al 2011;Crain et al 2013;Skory et al 2013): the results by Tornatore et al (2007) showed good agreement of metal abundances in simulated clusters in absence of AGN feedback at the price of significant over-production of galaxy stellar masses. More recent papers highlighted that much better agreement between stellar masses and cluster metallicities with observational results can be achieved when AGN feedback is included (Wiersma et al 2011;Crain et al 2013;Skory et al 2013).…”
Section: Comparison To Recent Simulationsmentioning
confidence: 99%
“…Moreover, energy and metal feedback that follows from supernova explosions should also be considered. Hydrodynamical simulations in which these physical processes have been taken into account (Muanwong et al 2002;Tornatore et al 2003;Valdarnini 2003;Kay et al 2004;Nagai et al 2007b) have shown that there is substantial agreement between the predicted ICM properties, such as the temperature profiles, and the corresponding measurements, though significant discrepancies still remain (Borgani & Kravtsov 2009). In particular, the model overpredicts the star mass fraction, which is found in simulations to be a factor ∼2−3 higher than that estimated from observations.…”
Section: Simulations With Cooling and Star Formationmentioning
confidence: 99%